Pengaruh Kreativitas, Media Sosial, dan Keterampilan Berwirausaha terhadap Keunggulan Bersaing UMKM Olahan Ikan Kecamatan Puger - Jamaludin, Achmad; Herlambang , Toni; Murtaliningtyas, Wenny (Pusat Riset dan Inovasi Nasional, 2025)
Fish processing MSMEs in Puger District, Jember Regency, have great potential to develop amidst the increasingly tight competition in the local food industry. However, many business actors still face challenges in maintaining and improving their competitiveness. This study aims to analyze the influence of creativity, social media, and entrepreneurial skills on the competitive advantage of fish processing MSMEs in the region. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected by distributing questionnaires to MSME actors and analyzed using the SPSS program. The results of the study showed that the three independent variables of creativity, social media, and entrepreneurial skills have a significant effect on competitive advantage. This finding indicates that improvements in these three aspects can drive MSME competitiveness more optimally. However, its effectiveness is still hampered by limited resources, low digital literacy, and minimal access to training. Therefore, cross-sector synergy is needed to strengthen the capacity of MSME actors so that they are able to compete sustainably.